CHARACTERISATION OF SEA-WATER INTRUSION IN THE PIONEER VALLEY, AUSTRALIA USING HYDROCHEMISTRY AND THREE-DIMENSIONAL NUMERICAL MODELLING - Werner A.D.; Gallagher M.R. (My University, 2006)
Sea-water intrusion is actively contaminating fresh groundwater reserves in the coastal aquifers of the Pioneer Valley, north-eastern Australia. A three-dimensional sea-water intrusion model has been developed using the MODHMS code to explore regional-scale processes and to aid assessment of management strategies for the system. A sea-water intrusion potential map, produced through analyses of the hydrochemistry, hydrology and hydrogeology, offsets model limitations by providing an alternative appraisal of susceptibility. Sea-water intrusion in the Pioneer Valley is not in equilibrium, and a potential exists for further landward shifts in the extent of saline groundwater. The model required consideration of tidal over-height (the additional hydraulic head at the coast produced by the action of tides), with over-height values in the range 0.5–0.9 m giving improved water-table predictions. The effect of the initial water-table condition dominated the sensitivity of the model to changes in the coastal hydraulic boundary condition. Several salination processes are probably occurring in the Pioneer Valley, rather than just simple landward sea-water advancement from “modern” sources of marine salts. The method of vertical discretisation (i.e. model-layer subdivision) was shown to introduce some errors in the prediction of water-table behaviour.
Keywords: SALT-WATER/FRESH-WATER RELATIONS; NUMERICAL MODELLING; COASTAL AQUIFERS; SALINATION; AUSTRALIA